This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The technique is to use L’Hopital’s rule to solve the limit.
Given,
x → 0 lim x 2 x − sin x = 0 0
which is undefined when 0 is substitute for x .
Thus, by applying L’Hopital’s rule, the derivative of the numerator and the
denominator is taken separately, then, take the limit of the function.
x → 0 lim x 2 x + ( − sin x ) = x → 0 lim [ 2 x 1 + ( − cos x ) ] = 0 1 + ( − 1 ) = 0 0
which is still undefined when the limit is evaluated.
Apply the rule again to yield, and take the limit.
x → 0 lim 2 x 1 + ( − cos x ) = x → 0 lim [ 2 sin x ] = 2 0 = 0
Since, the sin 0 ∘ = 0 and n 0 = 0 , where n is any integer and n = 0 . Therefore, the limit of the function is defined when x is approaches 0.